The critical role of informed political direction for advancing technology: The case of Swedish marine energy. (February 2017) - Andersson, Johnn; Perez Vico, Eugenia; Hammar, Linus; Sandén, Björn A.
Abstract: Marine energy technologies can contribute to meeting sustainability challenges, but they are still immature and dependent on public support. This paper employs the Technological Innovation Systems (TIS) framework to analyze the development and diffusion of Swedish marine energy up until 2014. While there were promising device developers, relevant industrial capabilities, and world-class research, the system suffered from weaknesses in several important innovation processes. Finally, the analysis identifies the lack of informed political direction as a critical blocking factor and highlights its connection to domestic market potential. Highlights: Sweden has promising device developers and world-class research in marine energy. The technology field is characterized by weaknesses in several innovation processes. Establishing an informed political direction may remove several blocking factors. Assessing the domestic market and export potentials is a necessary first step.